1992
DOI: 10.1159/000186939
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a Recombinant Hepatitis B Vaccine in Hemodialysis Patients: A Two-Year Follow-Up

Abstract: The immunogenicity of a recombinant hepatitis B vaccine was evaluated in 35 hemodialysis patients who received a standard dose (20 μg) of the vaccine at 0,1, 2 and 6 months. After the full vaccination course (month 7), 60% (21/35) of the patients had seroconverted (anti-HBs titer ≥10 mlU/ml). The duration of protection lasted up to 18 months after the start of vaccination in 85.7% (18/21) of the responders. At that time, an additional dose was given to all the patients: 1-2 months later, the overall immunizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
10
1
2
Order By: Relevance
“…Studies from other centers have reported a seroconversion rate of 23-33% after 3 doses of vaccine at 0. 1 and 2 months which after the fourth booster dose was 40% [5] and 62% [1], The seroconversion rate after 3 doses of vaccination in our patient population of 58% was higher than in these reports. Neither the age nor the duration of HD seem to correlate with the seroconver sion rate.…”
contrasting
confidence: 55%
“…Studies from other centers have reported a seroconversion rate of 23-33% after 3 doses of vaccine at 0. 1 and 2 months which after the fourth booster dose was 40% [5] and 62% [1], The seroconversion rate after 3 doses of vaccination in our patient population of 58% was higher than in these reports. Neither the age nor the duration of HD seem to correlate with the seroconver sion rate.…”
contrasting
confidence: 55%
“…DRB1*0301, DRB1*0701, and DQB1*0201 [5,8,9] were shown to have a higher prevalence in non-responders, whereas other antigens (DRB1*0101, *1301, *1501, and DPB1*0401) seem to mediate strong immune responses [9][10][11][12] . Higher age, obesity, male gender, smoking, and chronic dialysis are risk factors for a non-/ low-responsiveness [8,9,[13][14][15] .…”
Section: Resultsmentioning
confidence: 99%
“…There are few and little trials regarding the use of recombinant vaccine in HD subjects [5] in order to prevent HBV infection in this clinical set ting: they showed that the efficacy rate of a DNA-derived vaccine in the HD population is similar to the plasmaderived vaccines and lower than in healthy subjects [6]. The response rate to hepatitis B vaccine in HD patients is poor compared to healthy subjects for different reasons: the immunisation rate is lower, after completion of the vaccination schedule anti-HBs titers are lower and fall more rapidly [7], It has been calculated that anti-HBs lev els in the great majority of healthy vaccinées remain at higher than the minimal protective levels for about 5 years [8]: on the contrary, in HD patients about one third who respond to the vaccine program will become serone gative within 12 months of the first vaccine dose [7], Dif ferent schedules of DNA-derived vaccine have been pro posed in an attempt to increase the response rate: by intra muscular administration of multiple doses [9,10] or dou ble doses [11], by intramuscular administration inte grated with immunostimulators [12] or with intradermal injection [13], or by intradermal administration [14], Other authors proposed to modify the vaccine antigenic structure [15]: this observation has not been yet verified in HD subjects [16] and it has been partially confirmed in healthy subjects [17], However, many of these studies involved a very small number of HD patients, and the causes which have been shown to affect the HBV vaccine immunogenicity in HD subjects need more confirmation. Moreover, the persistence of anti-HBs in responder vacci nées and the factors which may influence the loss of antiHBs over time have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%